Limitations of Police Discretion In the Settlement of Criminal Cases of Domestic Violence - Rivaldi Abdullah (Estudiante Law Journal, 2026)
This study aims to identify and analyze the Use and Application of Police Discretion in Settlement of Domestic Violence Crimes. Then as one of the efforts to initiate legal determination related to these discretionary limits. This research is classified as normative research with a statute approach and case approach . The results of the study show that the application of police discretion has legality or legal basis according to the Criminal Procedure Code and Law Number 2 of 2002 concerning the Police of the Republic of Indonesia, and is used based on the principles of necessity, duty interests, objectives, and balance. Police discretion is generally limited by the public interest, necessary circumstances, and by laws and codes of ethics. For the settlement of domestic violence crimes, police discretion must be given legal determination regarding the limits, that as a crime the complaint must be victim-oriented, and victims of domestic violence cases must be kept away from so-called peaceful efforts so that the case does not recur.